2001
DOI: 10.1055/s-2001-18530
|View full text |Cite
|
Sign up to set email alerts
|

Hemoglobin Mass and Peak Oxygen Uptake in Untrained and Trained Residents of Moderate Altitude

Abstract: Blood composition, hemoglobin mass (CO rebreathing method) and VO2peak were measured in 15 untrained (UT-Bogotá) and 14 trained males (TR-Bogotá) living at 2600 m of altitude, and in 14 untrained lowlanders (UT-Berlin). [Hb] amounted to 15.3 + 0.2(SE) g/dl in UT-Berlin, 17.4 + 0.2 g/dl in UT-Bogotá and 16.0 + 0.2 g/dl in TR-Bogotá. Hb mass was significantly higher in UT-Bogotá (13.2 + 0.4 g/kg, P < 0.01) and in TR-Bogotá (14.7 + 0.5 g/kg, P < 0.001) than in UT-Berlin (11.7 + 0.2 g/kg). In TR-Bogotá also plasma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
51
2
8

Year Published

2003
2003
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(68 citation statements)
references
References 35 publications
(59 reference statements)
7
51
2
8
Order By: Relevance
“…In the younger groups of acclimatized SI, higher P a O 2 values compared to OI were observed that might be explained by reduced hypoxic ventilatory response with age (Kronenberg and Drage 1973). Our findings confirm previous studies performed on residents living at high altitude showing higher tHb and RCV (Bo¨ning et al 2001;Hurtado 1964;Sanchez et al 1970). RA exhibited an 11% higher tHb when compared to sea level dwellers (SL).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the younger groups of acclimatized SI, higher P a O 2 values compared to OI were observed that might be explained by reduced hypoxic ventilatory response with age (Kronenberg and Drage 1973). Our findings confirm previous studies performed on residents living at high altitude showing higher tHb and RCV (Bo¨ning et al 2001;Hurtado 1964;Sanchez et al 1970). RA exhibited an 11% higher tHb when compared to sea level dwellers (SL).…”
Section: Discussionsupporting
confidence: 93%
“…In our study we observed the well-known fact that RA subjects possess elevated [Hb] and Hct compared to SL subjects (Bo¨ning et al 2001;Sanchez et al 1970;Schmidt et al 1993). As a consequence of the higher RCV and the changes in PV mentioned above, [Hb] and Hct values were clearly increased in both groups exposed to intermittent hypoxia and were comparable to those found in RA.…”
Section: Pv Bv [Hb] and Hctsupporting
confidence: 90%
See 1 more Smart Citation
“…Additional data (Hb mass, blood volume) are published elsewhere (Böning et al 2001b). Informed consent was obtained from all participants, the study protocol was approved by the ethics committee of the faculty.…”
Section: Methodsmentioning
confidence: 99%
“…From the increase in Hb mass compared to sea level (approximately 12% in UT and 9% in TR, Böning et al 2001b;Robinson et al 2007) one might expect a corresponding increase in b nbi by only 2 mmol l -1 at rest. The effect should be larger because of two effects: extracellular volume and total body water seem to be reduced in highlanders (Ramirez et al 1998) as well as in sojourners (rev.…”
Section: Relation Between Be and [La] Changesmentioning
confidence: 96%